e-learning in the digital age.: The utility of the entrepreneurial self - Heidkamp, Birte; Kergel, David (Academic Quarter | Akademisk kvarter, 2016)
In the article we reconstruct the logic of utility and apply this concept to contemporary e-learning discourses. One main thesis is that a concept of neoliberal utility functions as a subtextual topic which influences these discourses: Not the objectives and needs of the actors define the utility of e-learning strategies, but neoliberal logic and its narration topoi. According to this neoliberal utility, anything that fosters the skills of the learner is considered as utile. The actor who actually defines why the skills are of vital importance is replaced by the discursive topoi of the neoliberal ideal-image of an entrepreneurial self. In a first step, the logic of utility will be reconstructed. Subsequently the influence of neoliberal logic on contemporary e-learning discourses is analysed via a discourse-analytical orientated approach.